Material handling selection for vise manufacturing using Hassan algorithm. Issue 1 (May 2020) - Sitepu, Muhammad Haikal; Alda, Tania; Nasution, Andri; Suci Amalia, Meilita Tryana Sembiring; Habibi, Anggi Ridho
Abstract: One type of transportation in industrial companies, for moving raw materials, semi-finished goods or finished goods from their original place to destination can be called as material handling. There are several material handling equipment available for manufacturing industry such as forklift, crane, conveyor, hand truck and trolley. However, not all material handling equipment are appropriate for specific manufacturing such as vise manufacturing. The selection of appropriate and efficient material handling equipment is important for reducing material handling cost. Around 20% of production cost is allocated for material handling activities. Vise consists of several part with different processes and materials. As the result, the flow of materials between processes are high. This paper aims to select appropriate material handling for vise manufacturing. Hassan's algorithm is used as a method for selecting material handling that consider various factors such as price, time and distances. Four types of material handling namely trolley, hand truck, wheeled rack, and hand pallet, are selected in this paper.